Investigation of the best artificial propagation technique for stingless bee Heterotrigona itama (Hymenoptera: Apidae: Meliponini) - Tan Shilan, Mohamad Syukri; Adam, Nur Azura; Jamian, Syari; Wan Mohd Adnan, Wan Nur Asiah; Samsudin, Siti Asma’ (Universiti Putra Malaysia Press, 2022)
Meliponiculture (keeping stingless bees) is a practice that is growing rapidly in the tropical and subtropical regions of the world. A limited number of studies regarding the technique would be most accurate in propagating the colonies to increase their numbers. Three different artificial propagation techniques were investigated in Ladang 10, Universiti Putra Malaysia. Three artificial propagation techniques, namely splitting, bridging, and splitting bridging, were conducted for eight consecutive weeks. Honey pot quantity and pollen pot quantity were recorded weekly for eight consecutive weeks. The success of colony division under different artificial propagation techniques and all the parameters taken were observed and recorded weekly. A significant difference (F = 15.04, df = 2, P = <.0001) was detected in the number of pollen pots between the different artificial propagation techniques, but not for the honey pot quantity (F = 0.22, df = 2, P = 0.8054). The bridging technique recorded the lowest pollen pot quantity while there was no significant difference in splitting and splitting-bridging techniques. The result showed that the splitting technique obtained new brood cells and queen of Heterotrigona itama. The splitting-bridging technique developed new brood cells without a new queen, whereas the bridging technique produced only pollen and honey pots. A matured queen’s presence can defeat the artificial propagation technique due to its pheromones function.